Comparative study on tensile and high cycle fatigue behaviour of 316L(N) SS hardfaced with Ni-Cr-B-Si alloy by GTA and laser cladding processes - Amruta Pasarkar; S. Balaguru (Nuclear Engineering and Technology)
In sodium-cooled fast reactors (SFR), 316L(N) SS grid plate is hardfaced with Ni-Cr-B-Si alloy to achieve higher wear resistance. Tensile and fatigue forces are acting at the interface between substrate and deposit due to different thermal expansion coefficients of those two materials, which can cause cracking of deposit and fracture during operation. Thus, it is very important to consider appropriate hardfacing method which can provide higher tensile and fatigue strength to avoid cracking/debonding at the interface. To find a solution to this problem, two hardfacing techniques, namely Gas Tungsten Arc (GTA) and Laser cladding (LC), are taken into consideration. Hardfaced specimens are prepared using each process on which tensile and high cycle fatigue tests are conducted. From the experimental testing, stress-strain and S-N curves are generated to predict the tensile and fatigue behaviour of specimens. Fractographic studies are conducted at fractured surfaces to understand the fatigue crack nucleation and propagation characteristics. The experimental results for both processes are compared. Tensile and fatigue strength of LC specimens are ∼11 % and ∼17 % less than those of GTA specimens due to its higher brittleness. Thus, GTA process is recommended as the efficient hardfacing process for grid plate of SFR.